NATIONAL CLINICAL GUIDELINE ON DIAGNOSIS AND TREATMENT OF HYPERTROPHIC CARDIOMYOPATHY - Editorial Article (Евразийский Кардиологический Журнал)
Developed on the instructions of the Russian Health Ministry, approved by the Society of Emergency Cardiology and the leading committee of Cardiology National clinical guidelines on diagnosis and treatment of hypertrophic cardiomyopathy working group: Chair of working group - prof. Ageev Ph.T. (Moscow), deputy chair of working group - MD Gabrusenko S.A. (Moscow), MD Postnov A.Y. (Moscow), RAS Academician Akchurin R.S. (Moscow), PhD Smirnova M.D. (Moscow) The Expert Committee: prof. Karpov R.S. (Tomsk), prof. Shaposhnik I.I. (Chelyabinsk), prof. LopatinYu.M. (Volgograd), prof. Barbarash O.L. (Kemerovo), prof. Galyavich A.S. (Kazan)